Cardiovascular risk in inflammatory arthritis: rheumatoid arthritis and gout (2020)
The increased risk of cardiovascular morbidity and mortality in rheumatoid arthritis and gout has been increasingly acknowledged in past decades, with accumulating evidence that gout, just as with rheumatoid arthritis, is an independent cardiovascular risk factor. Although both diseases have a completely different pathogenesis, the underlying pathophysiological mechanisms in systemic inflammation overlap to some extent. Following the recognition that systemic inflammation has an important causative role in cardiovascular disease, anti-inflammatory therapy in both conditions and urate-lowering therapies in gout are expected to lower the cardiovascular burden of patients. Unfortunately, much of the existing data showing that urate-lowering therapy has consistent beneficial effects on cardiovascular outcomes in patients with gout are of low quality and contradictory. We will discuss the latest evidence in this respect. Cardiovascular disease risk management for patients with rheumatoid arthritis and gout is essential. Clinical guidelines and implementation of cardiovascular risk management in daily clinical practice, as well as unmet needs and areas for further investigation, will be discussed.